Mapping of the Rsd Contact Site on the Sigma 70 Subunit of Escherichia coli RNA Polymerase - Jishage, Miki (American Society for Microbiology, 2001)
Rsd (regulator of sigma D) is an anti-sigma factor for the Escherichia coli RNA polymerase ς(70) subunit. The contact site of Rsd on ς(70) was analyzed after mapping of the contact-dependent cleavage sites by Rsd-tethered iron-p-bromoacetamidobenzyl EDTA and by analysis of the complex formation between Ala-substituted ς(70) and Rsd. Results indicate that the Rsd contact site is located downstream of the promoter −35 recognition helix-turn-helix motif within region 4, overlapping with the regions involved in interaction with both core enzyme and ς(70) contact transcription factors.